2022
DOI: 10.1097/nne.0000000000001320
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Remote Learning Modalities and Nursing Students' Perceptions of Their Sleep Quality During the COVID-19 Pandemic

Abstract: Background:The relationship between learning modalities and nursing students' sleep quality during the coronavirus disease (COVID-19) pandemic is unknown. Purpose: This study examined the relationships between remote learning and the sleep quality of nursing students during the COVID-19 pandemic. Methods: Using a cross-sectional descriptive design, 890 nursing students were surveyed online to identify sleeping habits and learning modalities. Results: There were no significant correlations between remote learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Evidence has revealed that college students' general perceptions of sleep quality may be influenced by factors such as age, gender, ethnicity, years of college, and work experience. [1][2][3][4][5][6][7][8][9] Ngo et al 5 found that age was the influential predictor of sleep quality, with younger nursing students having worse sleep quality. Gender differences also found that female college students tend to be prone to poor sleep quality and at high risk for sleep disturbances.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has revealed that college students' general perceptions of sleep quality may be influenced by factors such as age, gender, ethnicity, years of college, and work experience. [1][2][3][4][5][6][7][8][9] Ngo et al 5 found that age was the influential predictor of sleep quality, with younger nursing students having worse sleep quality. Gender differences also found that female college students tend to be prone to poor sleep quality and at high risk for sleep disturbances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evidence has revealed that college students’ general perceptions of sleep quality may be influenced by factors such as age, gender, ethnicity, years of college, and work experience 1-9. Ngo et al5 found that age was the influential predictor of sleep quality, with younger nursing students having worse sleep quality.…”
Section: Literature Reviewmentioning
confidence: 99%